THE EFFECT OF BRAND AWARENESS, LOCATION, AND SOCIAL MEDIA PROMOTIONS ON PURCHASING DECISIONS AT KEMARII! TRADITIONAL MODERN RESTAURANT - Samuel Lie; J.E Sutanto; Dicky Junartha Wirawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the effect of brand awareness, location, and social media promotion on purchasing decisions at Kemarii! Traditional Modern Restaurant. This study uses a quantitative approach with primary data obtained through the distribution of digital questionnaires using Google Forms. The population in this study is all consumers of Kemarii! Traditional Modern Restaurant, the number of which is unknown, so it is categorized as an infinite population. The sampling technique used non-probability sampling with the purposive sampling method. The sample size was determined using the 10-times rule, so that with 18 questions, 180 respondents were obtained as the research sample. Based on the results of the study, it was found that brand awareness, location, and social media promotion had a positive and significant effect on purchasing decisions. Therefore, restaurant managers are advised to strengthen marketing strategies that focus on increasing brand awareness and optimizing promotion through social media to attract consumer interest.